Estimations of plastic material damage on the rolling stock of city electrotransport - Зубенко, Денис Юрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The various deformations of plastic materials under the dynamic loads to study the effect on the kinematics and the accumulation of damage and material fracture durability with a further static tension on the rolling stock of the city electric transport have been shown